Synthesis, property, and application of carbon nanotube fiber - Lee, Sung-Hyun; Park, Ji Hong; Kim, Seung Min (Hanʼguk Seramik Hakhoe chi, 2021)
Carbon nanotube (CNT) fiber (CNTF), which is a collection of many CNTs aligned along the fiber axis, has attracted significant attention as a next-generation material with excellent properties. CNTF is a macroscopic material that potentially resembles the intrinsic properties of CNTs (high strength, conductivity, flexibility, etc.) that constitute it. Recent studies have shown that the specific strength of CNTF can reach 5.5 N/tex, which is much higher than that of the state-of-the-art carbon fiber (Toray T1100G, 3.9 N/tex) and the specific conductivity can reach 5640 S m 2 /kg, which is comparable to that of copper. This review first introduces the synthesis methods of CNTF, which can mainly be classified into three categories: forest spinning, direct spinning, and solution spinning. Each of the synthesis methods has its own merits and drawbacks, and the principles and characteristics of these methods are discussed. Second, various post-treatment methods to improve the properties of as-spun CNTFs are introduced. Without appropriate post-treatments, in the case of CNTFs fabricated by forest spinning and direct spinning, the properties cannot meet the demands for various applications. In particular, direct spinning combined with the appropriate post-treatment may potentially lead to the fabrication of CNTFs with excellent properties at relatively high productivity. Finally, the various application fields that can exploit the excellent characteristics of CNTF are introduced.